Interactions between bois noir and the esca disease complex in a Chardonnay vineyard in Italy - PAVAN, Francesco; CARGNUS, Elena; FRIZZERA, Davide; MARTINI, Marta; ERMACORA, Paolo (Phytopathologia Mediterranea, 2024)
Grapevine yellows bois noir (BN) and the grapevine trunk disease esca complex (EC) cause serious yield losses in European vineyards and are often widespread in the same vineyard. In a Chardonnay vineyard in north-eastern Italy, evolution of the two diseases from 2007 to 2020 was compared and their possible interaction was investigated. Evolution of symptomatic grapevines over the 16 years was very different between the two diseases, with a substantial linear increase for BN and an exponential increase for EC. The BN increase from one year to another was associated with the abundance of Hyalesthes obsoletus, the BN-phytoplasma vector, whereas the exponential increase in EC was likely due to the amount of inoculum and the increased size of pruning cuts over time. The courses of the two diseases were also very different, with a much greater occurrence of dead grapevines from EC than from BN. Some grapevines showed symptoms of both diseases, but the probability was less that a grapevine symptomatic for BN or EC showed symptoms of the other disease. Examinations of the spatial distribution of the two diseases showed dissociation between them. Data indicated that mechanisms of induced defense were involved in the lower probability that a grapevine affected by one showed symptoms of the other.